Is cheese making and marketing by farmers determining sustainability in dairy sheep? - Ruiz R.; Díez-Unquera B.; Beltrán de Heredia I.; Arranz J.; Mandaluniz N.; Ugarte E. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Since the beginning of the breeding programme for the Latxa and Carranzana dairy sheep in the middle 80s, significant changes have occurred in the production systems. A whole set of actors and advisory schemes have been implemented to increase productivity and efficiency, improving the standard of living of the farmers, food safety and quality of livestock products. However, whereas many flocks disappear without generational turnover, others decide to undertake new transformation and commercialisation strategies in an attempt to improve the economic turnover of the activity. Therefore cheese making and better access to the consumers are increasingly considered as key issues in the search for economic viability. An overview of the recent trends and current situation of the Latxa system in terms of its sustainability, with special emphasis on the role of cheese-making and marketing options will be presented in this paper.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)